Quality of systematic reviews in African emergency medicine : a cross-sectional methodological study - Van Niekerk, Jacques; Fapohunda, Tomiwa; Rohwer, Anke (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.